Perovskite light absorption layer preparation method and solar cell thereof
By using porous membrane frame heating technology in the preparation process of perovskite solar cells, the problems of crystallization quality and carrier composite defects of perovskite absorber layer are solved, the battery efficiency is improved and the process is simplified, which is suitable for large-scale production.
Patent Information
- Application Number
- CN202411106613.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-13
- Publication Date
- 2024-12-17
AI Technical Summary
During the large-area preparation process, perovskite solar cells face the problems of low crystallization quality of the light absorbing layer and many carrier recombination defects. The prior art lacks methods to simplify operating steps and reduce contaminated materials.
Precrystallization and nucleation is performed by coating the perovskite precursor wet film on the substrate where the carrier transport layer is deposited, and heated in a frame with a porous membrane, so that the perovskite precursor solution is affected. The crystallization is cured in the environment to prevent gas flow, thereby improving crystallization quality and reducing interface defects.
It significantly improves the photoelectric conversion efficiency of perovskite solar cells, reduces material pollution and costs, is suitable for large-scale production, simplifies process steps and improves material utilization.
Smart Images

Figure CN119156106A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solar cells, and in particular relates to a method for preparing a perovskite light-absorbing layer and a solar cell thereof. Background Art
[0002] As an emerging thin-film solar cell, perovskite solar cells have broad prospects in the fields of portable energy, indoor photovoltaics, and building photovoltaic integration due to their advantages such as low preparation cost, good weak light effect, high upper limit of photoelectric conversion efficiency, and the ability to prepare flexible devices. In particular, their photoelectric conversion efficiency increases rapidly, and small areas (<0.1cm 2 ) The certified photoelectric conversion efficiency (PCE) of single-junction perovskite solar cells has increased from 3.8% in 2009 to 26.1% in 2023, the certified photoelectric conversion efficiency of perovskite-perovskite tandem solar cells has reached 28%, and the certified photoelectric conversion efficiency of perovskite-crystalline silicon tandem solar cells has reached 33.9%.
[0003] However, in the process of rapid development towards industrialization, perovskite solar cells face problems such as low crystallization quality of large-scale perovskite light-absorbing layer films and many carrier recombination defects. Especially in the process of wet film solidification and crystallization during the solution method preparation process, the annealing process causes uneven grain size growth and many grain boundary defects, resulting in serious carrier recombination, which greatly affects the photoelectric conversion efficiency of the battery.
[0004] Chinese invention patent CN111933809B proposes a method of covering a wet film with a nanoscale covering film or a covering plate, and controlling the solvent evaporation rate to regulate crystallization. However, due to the direct contact between the cover plate and the wet film, this method has the problem that the wet film solution is easily adhered to the cover plate, and the polymers used, such as polyethersulfone, polyvinylidene fluoride and other membrane materials, are easily dissolved by solvents such as DMF, DMSO, GBL, NMP in the perovskite precursor solution, resulting in the problem that the covering film cannot be reused or impurities are introduced into the perovskite.
[0005] Patent publication number CN113745405A proposes a method of applying cover plate pressure to a perovskite film and then annealing the film. However, due to direct contact with the film, there may also be a problem of cover plate contamination.
[0006] Therefore, there is still a lack in the prior art of a method for preparing a perovskite light-absorbing layer film with improved crystallization quality, easy operation, and simple process. Summary of the invention
[0007] The purpose of the present invention is to overcome the shortcomings of the prior art and develop a method for preparing a perovskite light absorbing layer and a solar cell thereof, which not only simplifies the operation steps and reduces the possibility of contaminating materials, but also has the function of improving the crystallization quality of the light absorbing layer and reducing interface defects, thereby improving the performance of the perovskite solar cell.
[0008] The method for preparing the perovskite light-absorbing layer and the solar cell thereof according to the present invention comprises the following specific steps:
[0009] 1. A method for preparing a perovskite light-absorbing layer, the method comprising the following steps:
[0010] First, a perovskite precursor wet film is formed by coating on a substrate on which a carrier transport layer is deposited;
[0011] Then, a pre-crystallization nucleation operation is performed on the perovskite precursor wet film to form a nucleated film;
[0012] Then, the substrate with the nucleated film is placed in a frame with a porous film, and the nucleated film is heated to completely solidify and crystallize the film, so that the nucleated film is heated in the frame with the porous film;
[0013] Finally, the frame with the porous membrane is removed to complete the aforementioned heating annealing process.
[0014] The present invention has a breakthrough in that a porous membrane is arranged above and below the fully solidified crystal after pre-crystallization nucleation, so that the perovskite precursor solution is solidified and crystallized in a restricted environment. The precursor solution will evaporate gas, and the flow of gas can be suppressed in such an environment, and the flow of gas can be prevented in a direction, thereby improving the crystallization quality of the perovskite light-absorbing layer and reducing interface defects, thereby significantly improving the efficiency of the battery.
[0015] The substrate with the carrier transport layer deposited thereon is an electron transport layer such as tin dioxide and titanium dioxide, or a hole transport layer such as nickel oxide and PTAA, deposited on a conductive substrate of indium tin oxide ITO or conductive indium tin oxide FTO.
[0016] The perovskite precursor wet film is formed by coating a perovskite precursor solution, wherein the perovskite precursor solution is formed by dissolving perovskite light absorbing layer materials with different band gaps in an organic solvent.
[0017] The perovskite light-absorbing layer material is one or more of methylamine lead iodine, formamidine lead iodine, cesium lead iodine, etc.;
[0018] The organic solvent is one or more of 2-methoxyethanol, dimethylformamide, dimethyl sulfoxide and N-methylpyrrolidone.
[0019] The coating method of the perovskite precursor solution includes spin coating (including anti-solvent spin coating), blade coating, slit coating, spray coating, etc.;
[0020] The pre-crystallization nucleation operation includes one or more of vacuuming, air knife blowing, preheating, etc. It can be performed simultaneously or sequentially, such as vacuuming while heating, or heating while air knife blowing.
[0021] The top and bottom surfaces of the frame are both provided with porous membranes, the frame supports the porous membranes, the substrate with the nucleated film is placed on the porous membrane on the bottom surface of the frame, there is a gap between the porous membrane on the top surface of the frame and the nucleated film, and the frame with the porous membrane surrounds the upper and lower sides of the substrate. Specifically, the porous membrane on the top surface of the frame is parallel to the substrate and is 0.1 mm to 5 mm away from the substrate.
[0022] The frame is made of metal, rubber, wood or heat-resistant plastic and is a rectangular frame, and the middle of each side of the frame and the space inside are hollowed out;
[0023] The pore size of the porous membrane is 20 nm to 20 μm, and the porosity of the porous membrane is 25% to 80%;
[0024] The material of the porous membrane is solvent-resistant anodized aluminum AAO, stainless steel mesh, copper mesh, glass fiber membrane, polyimide membrane, nylon membrane, polypropylene membrane, polytetrafluoroethylene membrane, etc.
[0025] The heating conditions of the nucleated film are as follows: heating temperature of 70-150° C. and heating time of 1-30 min.
[0026] 2. A perovskite light-absorbing layer prepared by the above method.
[0027] 3. A perovskite solar cell, which is assembled by preparing a perovskite light-absorbing layer based on the above method, and then depositing another carrier transport layer, an interface buffer layer and a metal electrode on it in sequence.
[0028] The beneficial effects of the present invention compared to the prior art are as follows:
[0029] The present invention solves the problem of poor uniformity and many defects of the perovskite light absorption layer in the preparation process of the perovskite solar cell.
[0030] The present invention avoids mutual contamination of materials by using a solvent-resistant porous membrane with a high-temperature resistant frame, improves material utilization and work efficiency, reduces costs, and prepares a perovskite light-absorbing layer with large-sized grains, reduces interface defects, and improves battery efficiency.
[0031] The preparation method of the present invention has simple steps, mild conditions and strong repeatability. The prepared perovskite solar cell has high efficiency and is suitable for large-scale production, promotion and application.
[0032] The present invention can provide technical support for the industrialized production of large-area perovskite solar cells and is expected to produce good social and economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 A schematic diagram of a device used in the method for preparing a perovskite light-absorbing layer of the present invention;
[0034] Figure 2 This is a scanning electron microscope photo of the 100 nm pore size AAO (anodized aluminum oxide) porous membrane used in Example 1 of the present invention;
[0035] Figure 3 The scanning electron microscope images of the perovskite grain size in Example 2 and Comparative Example 2 of the present invention are compared, wherein (a) represents the scanning electron microscope grain morphology image of Comparative Example 2, and (b) represents the scanning electron microscope grain morphology image of Example 2;
[0036] Figure 4 The IV curves and performance parameter comparison table of the perovskite cells prepared in Example 3 and Comparative Example 3 of the present invention;
[0037] Figure 5 The efficiency distribution diagram of 30 perovskite battery devices prepared in Example 4 and Comparative Example 4 is statistically shown.
[0038] Figure 6 This is an IV curve diagram and a performance parameter comparison table of the perovskite cells prepared in Example 5 and Comparative Example 5 of the present invention. DETAILED DESCRIPTION
[0039] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the method described in the present invention is further described in detail through specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention, but do not mean that the present invention is limited to these embodiments.
[0040] like Figure 1 As shown, the device implemented in the present invention includes a frame 4 supporting a porous membrane, a porous membrane 5 and a heating platform 1, the porous membrane 5 is arranged on the top and bottom surfaces of the frame 4, the substrate and the liquid membrane 2 are arranged therein, the porous membrane 5 is located above the substrate and the liquid membrane 2, and the substrate and the liquid membrane 2, the frame 4, and the porous membrane 5 are placed as a whole on the heating platform 1.
[0041] When the heating platform 1 is working, it heats the substrate and the liquid film 2, and the perovskite precursor solution is volatilized by the heat to generate solvent vapor gas. A part of the solvent vapor will be blocked by the porous membrane 5 to form solvent vapor 3 that is blocked and rebounded by the porous membrane, and the other part will pass through the porous membrane 5 to form solvent vapor 6 that passes through the porous membrane. The perovskite precursor is dissolved and recrystallized by using the blocked and rebounded solvent vapor, which can fuse small grains into large grains, promote the transmission of photogenerated carriers, and improve the conversion efficiency of the battery.
[0042] The specific preparation method of the integral perovskite light absorbing layer solar cell of the present invention comprises the following specific steps:
[0043] 1) Prepare an ITO or FTO conductive substrate as a conductive substrate for a perovskite solar cell. Use deionized water, isopropyl alcohol and acetone to ultrasonically clean the ITO or FTO conductive substrate in sequence, and after drying, use a plasma cleaner or an ozone cleaner to treat the surface to improve the affinity for the liquid.
[0044] 2) Preparation of the first carrier transport layer film: Electron transport layers such as tin dioxide and titanium dioxide or hole transport layers such as nickel oxide and PTAA are uniformly deposited on a conductive substrate by spin coating, chemical bath deposition, magnetron sputtering, etc. and annealed to a thickness of 20 to 50 nm, so that the carrier transport layer is deposited.
[0045] 3) Preparation of perovskite light-absorbing layer. After coating the substrate with the carrier transport layer deposited with the perovskite precursor solution to form a wet film, the wet film is subjected to a pre-crystallization nucleation operation, and then a frame with a porous film is covered or placed on the nucleated film, the nucleated film is heated to completely solidify and crystallize, and the frame with the porous film is removed to complete the annealing process to prepare the perovskite light-absorbing layer.
[0046] 4) Preparation of the second carrier transport layer. Use spin coating, vacuum evaporation, etc. to uniformly deposit a hole transport layer such as Spiro-OMeTAD or an electron transport layer such as PCBM, C60, etc. on the perovskite light absorption layer with a thickness of 20 to 200 nm;
[0047] 5) Preparation of interface barrier buffer layer. Use vacuum evaporation, atomic layer deposition and other methods to uniformly deposit barrier layer materials such as BCP, LiF, Al2O3 on the substrate with a thickness of 1 to 8 nm;
[0048] 6) Electrode preparation: Electrodes such as gold, silver, and copper are deposited on the substrate using vacuum evaporation, magnetron sputtering, etc. to complete the assembly of the battery, with a thickness of 60 to 100 nm.
[0049] 7) Battery performance test.
[0050] Embodiments of the present invention are as follows:
[0051] Example 1: Preparation of perovskite light-absorbing layer using a stainless steel frame with a 100 nm pore size AAO (anodized aluminum oxide) porous membrane
[0052] (1) Use deionized water, isopropyl alcohol, and acetone to ultrasonically clean 2*2 cm ITO conductive glass for 20 minutes respectively, dry it in an oven at 60°C, and then put it in a plasma cleaner for 120 seconds.
[0053] (2) A 2 wt % SnO2 aqueous solution was spin coated on the ITO at a rotation speed of 4000 rpm / s for 25 s, and then annealed at 150° C. for 30 min, thereby forming a carrier transport layer on the upper surface of the ITO conductive glass.
[0054] (3) A mixture of 461 mg PbI2, 172 mg FAI and 20.3 mg MACl was dissolved in a mixed solvent of 800 μL DMF and 200 μL DMSO and stirred to dissolve to prepare a perovskite precursor solution.
[0055] 0.1 ml of perovskite precursor solution was dropped onto the carrier transport layer of ITO conductive glass, accelerated from 2000 rpm / s to 4000 rpm, and spin-coated for 20 seconds. In the last 5 seconds, 100 μL of chlorobenzene was added for pre-crystallization nucleation.
[0056] Then, a stainless steel frame with 100 nm pore size AAO on the top and bottom surfaces was placed on the nucleated film, and the nucleated film was heated at 150°C for 60 minutes to completely solidify and crystallize it. The stainless steel frame with AAO was removed to complete the annealing process.
[0057] (4) 90 mg of Spiro-OMeTAD was dissolved in 1 mL of CB, and 20 μL of Li-TFSI solution (500 mg / mL dissolved in acetonitrile), 10 μL of Co-TFSI solution (350 mg / mL dissolved in acetonitrile), and 40 μL of 4-tert-butylpyridine were added to prepare a hole transport layer solution. The solution was then dropped onto the perovskite film, accelerated from 2000 rpm / s to 3000 rpm, and spin coated for 45 s.
[0058] (5) Use vacuum coating machine, in <5*10 -4 Under a vacuum of 1.3 Pa, the interface barrier layer MoOx 3 nm was deposited at a rate of 0.03 nm / s.
[0059] (6) Use vacuum coating machine, in <5*10 -4 Pa vacuum, the silver electrode was deposited at a speed of 0.15nm / s to 80nm, and the effective area of a single subcell was 0.04cm 2 .
[0060] (7) The IV curve of the battery was tested using a 3A-level solar simulator, scanning from -0.2 V to 1.2 V. The photoelectric conversion efficiency of the battery prepared with the AAO porous membrane was 22.3%.
[0061] Comparative Example 1:
[0062] The difference between this comparative example and Example 1 is that in step (3), the stainless steel frame with AAO is not covered during solidification and crystallization.
[0063] The photoelectric conversion efficiency of the battery prepared in Comparative Example 1 is 21.1%.
[0064] Example 1: Scanning electron microscopy of 100 nm pore size AAO (anodized aluminum oxide) porous membrane prepared and used Figure 2 As shown in the figure, it can be seen that the pore size of AAO is about 100nm, and it runs through the upper and lower surfaces, which is conducive to the uniform passage of solvent vapor.
[0065] Example 2: Preparation of perovskite light-absorbing layer using a plastic frame with a 10 μm pore size stainless steel porous membrane
[0066] (1) Use deionized water, isopropyl alcohol, and acetone to ultrasonically clean 2*2 cm ITO conductive glass for 20 minutes respectively, dry it in an oven at 60°C, and then put it in a plasma cleaner for 120 seconds.
[0067] (2) A 4 mg / ml PTAA chlorobenzene solution was spin-coated on the ITO at a rotation speed of 5000 rpm / s for 40 s, and then annealed at 100° C. for 10 min to form a hole transport layer.
[0068] (3) A mixture of 461 mg PbI2, 172 mg FAI and 20.3 mg MACl was dissolved in a mixed solvent of 800 μL DMF and 200 μL DMSO and stirred to dissolve to prepare a perovskite precursor solution.
[0069] 0.1 ml of perovskite precursor solution was dropped onto ITO, accelerated from 2000 rpm / s to 4000 rpm, and spin-coated for 20 seconds. The perovskite film was pre-crystallized and nucleated by evacuating the pressure to 10 Pa within 30 seconds.
[0070] Then, a plastic frame with a stainless steel porous membrane with a pore size of 10 μm was placed on the nucleated film, and the nucleated film was heated at 150° C. for 60 minutes to completely solidify and crystallize it. The plastic frame with the stainless steel porous membrane was removed to complete the annealing process.
[0071] (4) Dissolve 20 mg of PCBM in 1 mL of CB to prepare an electron transport layer solution. Then drop the solution on the perovskite film and accelerate from 2000 rpm / s to 4500 rpm for spin coating for 30 s.
[0072] (5) Use vacuum coating machine, in <5*10 -4 Under a vacuum of 1.5 Pa, the interface barrier layer BCP 5 nm was deposited at a rate of 0.03 nm / s.
[0073] (6) Use vacuum coating machine, in <5*10 -4 Pa vacuum, the copper electrode is deposited at a speed of 0.15nm / s to a thickness of 100nm, and the effective area of a single subcell is 0.04cm 2 .
[0074] (7) The IV curve of the battery was tested using a 3A-level solar simulator, scanning from -0.2 V to 1.2 V. The photoelectric conversion efficiency of the battery prepared using a plastic frame with a stainless steel porous membrane was 22.8%.
[0075] The specific preparation process of the comparative sample corresponding to this embodiment is:
[0076] Comparative Example 2: The difference between this comparative example and Example 2 is that in step (3), the plastic frame with the stainless steel porous membrane is not covered during the solidification and crystallization.
[0077] The photoelectric conversion efficiency of the battery prepared in Comparative Example 2 is 21.5%.
[0078] The scanning electron microscope photos of the perovskite grain size in Example 2 and Comparative Example 2 are as follows: Figure 3 As shown in the figure, it can be seen that the grain size of Example 2 in (b) is significantly larger than the grain size of Comparative Example 2 in (a).
[0079] Example 3: Preparation of perovskite light absorbing layer using a rubber frame with a 0.45 μm glass fiber porous membrane
[0080] (1) Use deionized water, isopropyl alcohol, and acetone to ultrasonically clean 2*2 cm ITO conductive glass for 20 minutes respectively, dry it in an oven at 60°C, and then put it in an ozone cleaning machine for 15 minutes.
[0081] (2) A 4 mg / ml PTAA chlorobenzene solution was spin-coated on the ITO at a rotation speed of 5000 rpm / s for 40 s, and then annealed at 100° C. for 10 min to form a hole transport layer.
[0082] (3) A mixture of 461 mg PbI2, 172 mg FAI and 20.3 mg MACl was dissolved in a mixed solvent of 800 μL DMF and 200 μL DMSO and stirred to dissolve to prepare a perovskite precursor solution.
[0083] 0.05 ml of perovskite precursor solution was dropped onto ITO, and the perovskite solution was scraped onto the surface of the ITO substrate using a 100 μm four-sided preparation device. The perovskite film was pre-crystallized and nucleated using 100-degree hot air blowing.
[0084] Then, a rubber frame with a 0.45 μm glass fiber porous membrane was placed on the nucleated film, and the nucleated film was heated at 150° C. for 60 min to completely solidify and crystallize it. The rubber frame with the glass fiber porous membrane was removed to complete the annealing process.
[0085] (4) Use vacuum coating machine, in <5*10 -4 Pa vacuum, the electron transport layer C is deposited at a speed of 0.03nm / s 60 20nm.
[0086] (5) Use vacuum coating machine, in <5*10 -4 Under a vacuum of 1.5 Pa, the interface barrier layer BCP 5 nm was deposited at a rate of 0.03 nm / s.
[0087] (6) Use vacuum coating machine, in <5*10 -4 Pa vacuum, the silver electrode was deposited at a speed of 0.15nm / s to 80nm, and the effective area of a single subcell was 0.04cm 2 .
[0088] (7) The IV curve of the battery was tested using a 3A-level solar simulator, scanning from -0.2 V to 1.2 V. The photoelectric conversion efficiency of the battery prepared using a rubber frame with a glass fiber porous membrane was 22.6%.
[0089] The specific preparation process of the comparative sample corresponding to this embodiment is:
[0090] Comparative Example 3: The difference between this comparative example and Example 3 is that in step (3), the rubber frame with the glass fiber porous membrane is not covered during the solidification and crystallization.
[0091] The photoelectric conversion efficiency of the battery prepared in Comparative Example 3 is 21.7%.
[0092] The IV curve results of the perovskite cells prepared in Example 3 and Comparative Example 3 are as follows: Figure 4As shown in the figure, it can be seen that due to the use of a rubber frame with a porous membrane in the curing and crystallization process of Example 3, the short-circuit current and the fill factor are significantly improved compared with Comparative Example 3. This is because the crystallization quality of the perovskite is improved, the photogenerated carrier recombination defects are reduced, and the carriers collected by the photovoltaic cell electrodes are increased.
[0093] Example 4: Preparation of perovskite light-absorbing layer using a wooden frame with a 0.22 μm polypropylene porous membrane
[0094] (1) Use deionized water, isopropyl alcohol, and acetone to ultrasonically clean 2*2 cm ITO conductive glass for 20 minutes respectively, dry it in an oven at 60°C, and then put it in an ozone cleaning machine for 15 minutes.
[0095] (2) A 3 wt % nickel oxide aqueous solution was spin-coated on the ITO at a rotation speed of 4000 rpm / s for 25 s, and then annealed at 300° C. for 50 min to form a hole transport layer.
[0096] (3) A mixture of 461 mg PbI2, 172 mg FAI and 20.3 mg MACl was dissolved in a mixed solvent of 800 μL DMF and 200 μL DMSO and stirred to dissolve to prepare a perovskite precursor solution.
[0097] 0.05 ml of perovskite precursor solution was dropped onto ITO, and the perovskite solution was scraped onto the surface of the ITO substrate using a 100 μm four-sided preparation device. The perovskite film was pre-crystallized and nucleated using 100-degree hot air blowing.
[0098] Then, a wooden frame with a 0.22 μm polypropylene porous membrane was placed on the nucleated film, and the nucleated film was heated at 150° C. for 60 min to completely solidify and crystallize it. The wooden frame with the polypropylene porous membrane was removed to complete the annealing process.
[0099] (4) Dissolve 20 mg of PCBM in 1 mL of CB to prepare an electron transport layer solution. Then drop the solution on the perovskite film and accelerate from 2000 rpm / s to 4500 rpm for spin coating for 30 s.
[0100] (5) Use vacuum coating machine, in <5*10 -4 Under a vacuum of 1.5 Pa, the interface barrier layer BCP 5 nm was deposited at a rate of 0.03 nm / s.
[0101] (6) Then, 80 nm of silver electrode was deposited at a rate of 0.15 nm / s. The effective area of a single subcell was 0.04 cm 2 .
[0102] (7) The IV curve of the cell was tested using a 3A-level solar simulator, scanning from -0.2 V to 1.2 V, and the photoelectric conversion efficiency of the cell prepared using a wooden frame with a polypropylene porous membrane was recorded.
[0103] The specific preparation process of the comparative sample corresponding to this embodiment is:
[0104] Comparative Example 4: The difference between this comparative example and Example 4 is that in step (3), the wooden frame with the polypropylene porous film is not covered during the solidification and crystallization.
[0105] Example 4 and Comparative Example 4 respectively prepared 30 perovskite battery devices with efficiency distribution as follows Figure 5 As shown in the figure, it can be seen that in Example 4, a wooden frame with a polypropylene porous membrane was used during the solidification and crystallization process.
[0106] Relative to Comparative Example 4, the efficiency statistical distribution is clearly shifted toward higher efficiency.
[0107] Example 5: Preparation of a perovskite light-absorbing layer using a stainless steel frame with a 0.22 μm polytetrafluoroethylene porous membrane
[0108] (1) Use deionized water, isopropyl alcohol, and acetone to ultrasonically clean 2*2 cm ITO conductive glass for 20 minutes respectively, dry it in an oven at 60°C, and then put it in a plasma cleaner for 2 minutes.
[0109] (2) A 2.5 mg / ml PTAA toluene solution was spin-coated on the ITO at a rotation speed of 6000 rpm / s for 40 s, and then annealed at 100° C. for 10 min to form a hole transport layer.
[0110] (3) A mixture of 461 mg PbI2, 172 mg FAI and 20.3 mg MACl was dissolved in a mixed solvent of 800 μL DMF and 200 μL DMSO and stirred to dissolve to prepare a perovskite precursor solution.
[0111] 0.05 ml of perovskite precursor solution was dropped onto ITO, and the perovskite solution was scraped onto the surface of the ITO substrate using a 100 μm four-sided preparation device. The perovskite film was pre-crystallized and nucleated using 100-degree hot air blowing.
[0112] Then, a stainless steel frame with a 0.22 μm polytetrafluoroethylene porous membrane was placed on the nucleated film, and the nucleated film was heated at 150° C. for 60 min to completely solidify and crystallize it. The stainless steel frame with the polytetrafluoroethylene porous membrane was removed to complete the annealing process.
[0113] (4) Use vacuum coating machine, in <5*10 -4 Pa vacuum, the electron transport layer C is deposited at a speed of 0.03nm / s60 25nm.
[0114] (5) Use vacuum coating machine, in <5*10 -4 Under a vacuum of 1.5 Pa, the interface barrier layer BCP 5 nm was deposited at a rate of 0.03 nm / s.
[0115] (6) Use vacuum coating machine, in <5*10 -4 Pa vacuum, the silver electrode was deposited at a speed of 0.15nm / s to 80nm, and the effective area of a single subcell was 0.04cm 2 .
[0116] (7) The IV curve of the battery was tested using a 3A-level solar simulator, scanning from -0.2 V to 1.2 V. The photoelectric conversion efficiency of the battery prepared using a stainless steel frame with a polytetrafluoroethylene porous membrane was 24.7%.
[0117] The specific preparation process of the comparative sample corresponding to this embodiment is:
[0118] Comparative Example 5: The difference between this comparative example and Example 5 is that in step (3), the stainless steel frame with the polytetrafluoroethylene porous membrane is not covered during the solidification and crystallization.
[0119] The photoelectric conversion efficiency of the battery prepared in Comparative Example 5 is 23.7%.
[0120] The IV curve results of the perovskite cells prepared in Example 5 and Comparative Example 5 are as follows: Figure 6 As shown in the figure, it can be seen that in Example 5, due to the use of a stainless steel frame with a polytetrafluoroethylene porous membrane in the solidification and crystallization process, the open circuit voltage, short circuit current and fill factor are significantly improved compared with Comparative Example 5. This is because the crystallization quality of the perovskite is improved, the photogenerated carrier recombination defects are reduced, and the carriers collected by the photovoltaic cell electrodes are increased.
[0121] In the technical situation of the perovskite solar cell of the present invention, due to the existence of a theoretical limit, that is, the maximum efficiency of a single-junction cell is 33%. The closer to the theoretical efficiency, the more difficult it is to achieve and repeat. Therefore, it is not easy for technical personnel in this field to improve the cell photoelectric conversion efficiency of the perovskite solar cell by 1%.
[0122] The present invention has confirmed through the above experiments and tests that the photoelectric conversion efficiency of the battery can be significantly improved by 1%, which will greatly improve the performance of the overall battery.
[0123] The above specific implementation modes are used to explain the present invention rather than to limit the present invention. Any modification and change made to the present invention within the spirit of the present invention and the protection scope of the claims shall fall within the protection scope of the present invention.
[0124] The above description is only a preferred embodiment of the present invention, so all equivalent changes or modifications made according to the structure, characteristics and principles described in the scope of the patent application of the present invention are included in the scope of the patent application of the present invention.
Claims
1. A method for preparing a perovskite light-absorbing layer, characterized in that: The method comprises the following steps: First, a perovskite precursor wet film is formed by coating on a substrate on which a carrier transport layer is deposited; Then, a pre-crystallization nucleation operation is performed on the perovskite precursor wet film to form a nucleated film; Then, the substrate with the nucleated film is placed in a frame with a porous film, and the nucleated film is heated to completely solidify and crystallize it; Finally, the frame with the porous membrane is removed to complete the annealing process.
2. The method for preparing a perovskite light absorbing layer according to claim 1, characterized in that: The substrate with the carrier transport layer deposited thereon is an electron transport layer such as tin dioxide and titanium dioxide, or a hole transport layer such as nickel oxide and PTAA, deposited on a conductive substrate of indium tin oxide ITO or conductive indium tin oxide FTO.
3. The method for preparing a perovskite light absorbing layer according to claim 1, characterized in that: The perovskite precursor wet film is formed by coating a perovskite precursor solution, wherein the perovskite precursor solution is formed by dissolving perovskite light absorbing layer materials with different band gaps in an organic solvent.
4. The method for preparing a perovskite light absorbing layer according to claim 3, characterized in that: The perovskite light absorbing layer material is one or more of methylamine lead iodine, formamidine lead iodine, and cesium lead iodine; The organic solvent is one or more of 2-methoxyethanol, dimethylformamide, dimethyl sulfoxide and N-methylpyrrolidone.
5. The method for preparing a perovskite light absorbing layer according to claim 1, characterized in that: The coating method of the perovskite precursor solution includes spin coating (including anti-solvent spin coating), blade coating, slit coating, and spray coating; The pre-crystallization nucleation operation includes one or more of vacuuming, air knife blowing, and pre-heating.
6. The method for preparing a perovskite light absorbing layer according to claim 1, characterized in that: The top and bottom surfaces of the frame are both provided with porous membranes, and the substrate with the nucleated film is placed on the porous membrane on the bottom surface of the frame, with a gap between the porous membrane on the top surface of the frame and the nucleated film.
7. The method for preparing a perovskite light absorbing layer according to claim 6, characterized in that: The frame is made of metal, rubber, wood or heat-resistant plastic; The pore size of the porous membrane is 20 nm to 20 μm, and the porosity of the porous membrane is 25% to 80%; The material of the porous membrane is solvent-resistant anodized aluminum AAO, stainless steel mesh, copper mesh, glass fiber membrane, polyimide membrane, nylon membrane, polypropylene membrane, and polytetrafluoroethylene membrane.
8. The method for preparing a perovskite light absorbing layer according to claim 1, characterized in that: The heating conditions of the nucleated film are as follows: heating temperature of 70-150° C. and heating time of 1-30 min.
9. A perovskite light absorbing layer, characterized in that: The invention is prepared by the method according to any one of claims 1 to 8.
10. A perovskite solar cell, characterized in that , After the perovskite light-absorbing layer is prepared based on the method described in claim 1, another carrier transport layer, an interface buffer layer and a metal electrode are sequentially deposited thereon to assemble a perovskite solar cell.
Citation Information
Patent Citations
A thin film drying method and its application
CN111933809B
Preparation method and solar cell of perovskite thin film
CN113745405A
